Botanical fuel oxygenate compositions - HERNDON CARLA G (2013)
Botanically derived compositions of fuel oxygenates are provided, as well as methods of making the same. The compositions are produced from extracts of plant tissues, and unexpectedly contain aliphatic ethers and alcohols in useful concentrations. These compositions represent sources of oxygenates such as MTBE, ETBE, DIPE, TAME, ETBE and TBA from non-mineral sources, allowing them to be produced domestically in countries without mineral hydrocarbon resources and allowing them to be combusted without any net addition of carbon dioxide to the atmosphere.